Studi Komparasi Antara Model Team AssistedIndividualization Dan Team Games TournamentTerhadap Hasil Belajar Matematika SiswaKelas IV DI SD N 05 KaranganyarTahun Ajaran 2015/2016 - Syakroni, Syakroni (2016)
Abstract Syarkroni, A510120081, A COMPARATIVE STUDY BEETWEN OF TEAM ASSISTED INDIVIDUALIZATION MODELS AND TEAMS GAMES TOURNAMENT TO LEARNING OUTCOMES OF MATHEMATICS IN 4th GRADE SD N 05 KARANGANYAR SCHHOL YEAR 2015/2016 Skripsi. The Faculty of Teacher Training and Education Sciencee, University Muhammadiyah Surakarta. February, 2016. This study aims to determine: (1)different influence TAI models and TGT to learning outcomes of mathematics in 4th grade of SD N 05 Karanganyar. (2)greater influence of TAI models and TGT to learning outcomes of mathematics in class IV SD N 05 Karanganyar. This study using quantitative study with an experimental model. His research is student of 4th grade SD N 05 Karanganyar scholl year 2015/2016. The data colection technique using the test, documentation, and interview. Technique of analysis using t test were preceded by the prerequisite test analysis is test for normality. Based on analysis eith significance level of 5% was obtained